THE IMPACT OF QIRĀ’ĀT VARIATIONS ON THE VERSE: WA-ĀYATUN LAHUMU AL-LAYLU NASLAKHU MINHU AN-NAHĀRA (YĀ SĪN: 37) AND ITS REFLECTIONS IN SCIENTIFIC EXEGESIS: - Muhammad Diaz Supandi; Alfan Arif Rabbani; Muhammad Bili Syaputra; Aqdi Rofiq Asnawi; Ahmad Fadhilul (Al-Majaalis : Jurnal Dirasat Islamiyah, 2025)
This research arises from a lack of in-depth research on the role of qirā'āt variations in enriching the scientific interpretation (tafsīr 'ilmī) of the Qur'an, particularly in cosmological verses. One example is the statement of Allah Wa āyatun lahumu al-laylu naslakhu minhu an-nahār (Yā-sīn: 37), which has three main qirā'āt: naslakhu (qirā'ah al-jumhūr), yuslakhu (qirā'ah Ibn 'Āmir), and taslakhu (qirā'ah Abī Ja'far). This study aims to reveal the semantic and bayānī meanings of these variations of reading and relate them to modern scientific phenomena regarding the day-night cycle. The research method used is qualitative, based on library research, with textual-comparative analysis of classical qirā'āt texts, traditional tafsīr works, and contemporary scientific interpretive literature. The findings show that the variety of readings provides complementary layers of meaning: naslakhu emphasizes the direct role of Allah as the regulator of cosmic phenomena; Yuslakhu highlights the firmness and orderliness of natural law; While Taslakhu offers dynamic visual illustrations that depict the night actively covering the day. The contribution of this research shows that the science of qirā'āt not only preserves textual authenticity but also expands the horizons of scientific interpretation by presenting an integrated theological, linguistic, and scientific perspective.